2018
DOI: 10.29252/jafm.11.04.28175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fin Geometry on Flow-Induced Vibration Response of a Finned Tube in a Tube Bundle

Abstract: An experimental study is carried out on a parallel triangular finned tube array with P/Deff ratio 1.62 to examine the effect of fin geometry on flow-induced vibration response. Fins on a tube increase the heat transfer rate but these also affect the fluid dynamics around the tube. The flow pattern across the finned tubes is complex as compared to bare tube arrays. There are numerous parameters that affect the finned tube vibration subjected to air cross-flow in a tube array. In the current study, some of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
4
12
0
Order By: Relevance
“…Arshad et al. 16 carried out a wind tunnel study on a parallel triangular finned tube array with effective pitch ratio of 1.62. They studied the effect of fin thickness, fin density, and tube location on fluid elastic instability.…”
Section: Introductionmentioning
confidence: 99%
“…Arshad et al. 16 carried out a wind tunnel study on a parallel triangular finned tube array with effective pitch ratio of 1.62. They studied the effect of fin thickness, fin density, and tube location on fluid elastic instability.…”
Section: Introductionmentioning
confidence: 99%
“…Bernitsas et al (2008), developed a device called VIVACE and conducted VIV tests to investigate its performance, and Lee and Bernitsas (2011), used this VIVACE converter to obtain renewable energy. Arshad et al (2018) investigated the effect of fin geometry on VIV response. They especially focused on fin thickness and fin density.…”
Section: Introductionmentioning
confidence: 99%
“…Jandaud et al (2016) has done the geometrical optimization of a three-dimensional CFD modelled heat sink using Variable Neighbourhood Search method in order to minimize the pressure drop and thermal resistance of the system. Arshad et al (2018) has done the experimental study to observe the effect of fin geometry on flow-induced vibration response using parallel triangular finned tube array with P/Deff ratio as 1.62. The authors found that instability threshold is delayed with the increment in fin density.…”
Section: Introductionmentioning
confidence: 99%